1996
DOI: 10.1074/jbc.271.42.26157
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Catalytic Subunit of cAMP-dependent Protein Kinase in Complex with Isoquinolinesulfonyl Protein Kinase Inhibitors H7, H8, and H89

Abstract: The discovery of several hundred different protein kinases involved in highly diverse cellular signaling pathways is in stark contrast to the much smaller number of known modulators of cell signaling. Of these, the H series protein kinase inhibitors (1- Isoquinolinesulfonamide protein kinase inhibitors of the H series are among the most widely used inhibitors of Ser/Thr kinases and are indispensable in cellular and signal transduction research. Protein phosphorylation (central to cellular regulation) is mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
245
1
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 264 publications
(259 citation statements)
references
References 49 publications
9
245
1
3
Order By: Relevance
“…We found that the competitive ATP antagonist H89 that is generally accepted to be a potent PKA inhibitor [47] decreased metachromatic matrix accumulation compared to untreated control cultures, and mechanical load was only partially able to rescue the diminished cartilage formation, suggesting that although the PKA pathway was required for mechanical load-induced matrix formation, the involvement of other mechanosensitive pathways is likely. Indeed, H89-treatment reduced the amount of P-Sox9 (at Ser 211) in differentiating chondrocytes, which could not be compensated by mechanical stimuli.…”
Section: Discussionmentioning
confidence: 87%
“…We found that the competitive ATP antagonist H89 that is generally accepted to be a potent PKA inhibitor [47] decreased metachromatic matrix accumulation compared to untreated control cultures, and mechanical load was only partially able to rescue the diminished cartilage formation, suggesting that although the PKA pathway was required for mechanical load-induced matrix formation, the involvement of other mechanosensitive pathways is likely. Indeed, H89-treatment reduced the amount of P-Sox9 (at Ser 211) in differentiating chondrocytes, which could not be compensated by mechanical stimuli.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, most of the 14 amino acids of the porcine PKA catalytic subunit implicated in the H89 drug binding [26] are conserved, with the exception that M120 and Y122 (porcine numbering) are substituted by L112 and F114 (P. falciparum numbering) in the parasite enzyme (Fig. 6B).…”
Section: Discussionmentioning
confidence: 99%
“…These residues are important shape determinants for the ATP-binding cavity of ROCK. Azaindole 1 fits nicely into the X-ray crystal structure of ROCK-1 (co-crystal with fasudil, 2esm.pdb, subunit A (Jacobs et al, 2006)), while it cannot be docked well into PKA (co-crystal with H89, 1ydt.pdb, (Engh et al, 1996)). The inability of azaindole 1 to bind strongly to PKA can be attributed to four key mutations (Figure 4), three of which are part of the residue combination that makes ROCK unique (see above).…”
Section: Docking Azaindole 1 In a Rock-modelmentioning
confidence: 92%